2016
DOI: 10.1111/jgs.14264
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Functional Disability in the Oldest Adults in China

Abstract: This study examined patterns of onset of activity of daily living (ADL) disability in a nationally representative sample of older adults in mainland China. Using longitudinal data from the Chinese Longitudinal Healthy Longevity Survey from 1998 to 2008 (N = 5,570), nonparametric methods were used to evaluate median age at onset of various ADL disabilities and differences in the incidence of disabilities according to sex. The sampled older Chinese adults developed ADL disabilities, on average, between the ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Interviewers asked participants if they needed personal assistance in performing five activities (bathing, transferring, dressing, eating, and toileting) or had problems with incontinence (12). ADL disability was defined as being incontinent or needing assistance in performing one or more of the five other activities (12,15,16). Severe ADL disability was defined as having disability in three or more of the six activities (7).…”
Section: Measures Disabilitymentioning
confidence: 99%
“…Interviewers asked participants if they needed personal assistance in performing five activities (bathing, transferring, dressing, eating, and toileting) or had problems with incontinence (12). ADL disability was defined as being incontinent or needing assistance in performing one or more of the five other activities (12,15,16). Severe ADL disability was defined as having disability in three or more of the six activities (7).…”
Section: Measures Disabilitymentioning
confidence: 99%
“…As one ages, health problems accumulate and people start to lose their ability to perform activities of daily living (ADLs), such as dressing, using the toilet, bathing, and eating. Past studies have shown that the pattern of ADL disability in geriatric populations follows a distinct progression [19]. These hierarchical patterns of functional decline or ADL scales – typically established using item response theory (IRT) methods and hazard models – have been reliably and validly assessed not only for the institutionalized population but also more generally for community-dwelling older adults [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mortality and morbidity data in the CLHLS have been found to be of good quality (Zeng, 2012) and have been used in many studies analysing health patterns of older Chinese (e.g. Peng et al ., 2010; Peng & Wu, 2015; Fong & Feng, 2016). With a sample size of over 128,000 exposure years we are able to estimate separate models for male and female residents in both urban and rural areas.…”
Section: Introductionmentioning
confidence: 99%